The Influence of the Discovery Learning Model on Writing Skills for Observation Report Texts - Giska Mardatillah Zikra; Silvia Permatasari; Tria Putri Mustika; Mangatur Sinaga (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Discovery learning is a student-centered learning model that encourages students to discover concepts, principles, or knowledge for themselves through exploration, observation, and active problem-solving. This method shifts the teacher's role from a source of information to a facilitator, aiming to improve in-depth understanding, critical thinking skills, and long-term memory retention. This study aims to see the effect of the discovery learning model on the ability to write observational report texts. This study was conducted at SMK Muhammadiyah 3 Terpadu Pekanbaru in the odd semester of the 2025/2026 academic year. This study used a quantitative descriptive method based on quasi-experiments using one group pretest and posttest design. The population in this study were all 10th grade students who participated in the learning of the ability to write observational report texts using the discovery learning model, totaling 34 students while the sample in this study amounted to 31 students selected using a simple random technique. The instrument in this study was a test to write observational report texts involving the completeness of the text content, text structure, and linguistic rules as indicators in the assessment rubric. Data analysis used the Wilcoxon test because the data were not normally distributed. The results showed an increase in students' ability to write observational report texts after the implementation of the discovery learning model. The Asymp. sig. (2-tailed) value was smaller than 0.05 so it can be concluded that the discovery learning model had a significant effect on writing observational report texts for 10th grade students of SMK Muhammadiyah 3 Terpadu Pekanbaru.